2010
DOI: 10.1007/s12519-010-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

One day hospitalization after open, double-J stented pyeloplasty

Abstract: Transanastomotic stenting with double-J catheter is recommended as the reasonable mode of drainage in open pyeloplasty in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…18 In contrast, some authors stated that the nonstented group had a shorter hospital stay than the stented group. 8,12,14,15,[23][24][25][26][27] However in our study the length of stay for both stented and non-stented patients was nearly the same (3 days) ( Table 2). Most of the patients in our study were from rural area and were poor economically, so we kept the patients in ward until perinephric drain was removed.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…18 In contrast, some authors stated that the nonstented group had a shorter hospital stay than the stented group. 8,12,14,15,[23][24][25][26][27] However in our study the length of stay for both stented and non-stented patients was nearly the same (3 days) ( Table 2). Most of the patients in our study were from rural area and were poor economically, so we kept the patients in ward until perinephric drain was removed.…”
Section: Discussionmentioning
confidence: 73%
“…Some authors reported similar results with a shorter hospital stay in the stented group. 3,[18][19][20][21][22][23] Elmalik et al also explained this difference on the basis of keeping patients with PUL (urinoma) in patient. 18 In contrast, some authors stated that the nonstented group had a shorter hospital stay than the stented group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations